Early death prediction in children with traumatic brain injury using computed tomography scoring systems. (January 2022) - Mohamed Hussein, Nimo; Zhu, Pingyi; Meng, Shuang; Wang, Yu; Zhao, Pinghui; Li, Lan; Shu, Kun; Zou, Pinfa; Lin, Lulu; Shen, Liting; Xia, Yikai; Tang, Jing; et al.
Highlights: Retrospective study of predicting the outcome of severe traumatic brain injury of children. Comparison the ability of Marshall and Rotterdam CT scoring systems to predict the early death in children with traumatic brain injury. Marshall scoring system performs equally to or significantly better than the Rotterdam scoring system in children. Basal cistern absence and voluminous mass lesion are most significant indicators of early death among CT findings in children with severe traumatic brain injury. Abstract: Purpose: Marshall and Rotterdam are the most commonly used CT scoring systems to predict the outcome following traumatic brain injury (TBI). Although several studies have compared the performance of the two scoring systems in adult patients, none of these studies has evaluated the performance of the two scoring systems in pediatric patients. This study aimed to determine the predictive value of the Marshall and Rotterdam scoring systems in pediatric patients with TBI. Methods: This retrospective study included 105 children with admission GCS < 12, with a mean age of 6.2 (±3.5) years. Their initial CT and status at hospital discharge (dead or alive) were reviewed, and both the Marshall and Rotterdam scores were calculated. We examined whether each score was related to the early death of pediatric patients. Results: The pediatric patients with higher Marshall and Rotterdam scores had a higher mortality rate. There was a good correlation between the Marshall and Rotterdam scoring systems (Spearman's rho = 0.618, significant at the 0.05 level). Both systems demonstrated a high degree of discrimination when predicting early mortality. The Marshall scoring system had reasonable discrimination (AUC 0.782), and the Rotterdam scoring system had good discrimination (AUC 0.729). Comparing the two CT scoring systems, the Marshall scoring system provided a better positive predictive value (90%) for early mortality than the Rotterdam scoring system (78%). Conclusions: Both the Marshall and Rotterdam scoring systems have good predictability for assessing mortality in pediatric patients with TBI. The performance of the Marshall scoring system was equal to or slightly better than that of the Rotterdam scoring system.